Antibacterial Activity Test of Moringa Leaf Ethanol Extract Ointment of Moringa oleifera Lamk. on Staphylococcus aureus Bacteria - Miladiarsi; Nasrawati Basir; Nurlindasari; Wahdaniar; Ade Irma (Journal of Health Sciences and Medical Development, 2023)
Staphylococcus aureus is gram-positive bacteria and can cause infections and disorders of the skin. This study aims to determine the physical stability of ointment preparations containing ethanol extract from Moringa leaves based on variations in concentration and antibacterial activity against Staphylococcus aureus. This research is a laboratory experiment with the stages of making an ointment from the ethanol extract of Moringa leaves and testing its antibacterial activity against Staphylococcus aureus. Data analysis using One-Way ANOVA. The results of the research on moringa leaf ethanol extract ointment preparations were physically and chemically stable through organoleptic testing, homogeneity, dispersion, viscosity, and pH by including a cycling test. Antibacterial activity test showed that moringa leaf ointment had antibacterial activity against Staphylococcus aureus with the diameter of the inhibition zone each extract concentration of 15% (16.1mm), 20% extract concentration (17.3mm), 25% extract concentration (18.1mm) in inhibiting bacteria staphylococcus aureus. Ethanol extract ointment preparations with each concentration have a strong category of inhibition against the Staphylococcus aureus bacteria.